Efficient production of the flavoring agent zingerone and of both (r)- and (s)-zingerols via green fungal biocatalysis: comparative antifungal activities between enantiomers - Svetaz, Laura A. (2014)
Fil: Svetaz, Laura A. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas; Argentina